The Effect of Assertiveness Training on Improving Psychological Well-Being - Kamilah, Walia; Maghfiroh, Nasruliyah Hikmatul; Suharmawan, Wahid (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
The Effect of Assertiveness Training on Improving Psychological Well-Being. Research examines the effect of assertive training to improve psychological well-being at the Al Quran Ibnu Katsir 2 Jember Islamic boarding school. The aim of this research is to determine the effectiveness of using assertiveness training to improve psychological well-being. The research approach uses quantitative methods with a pre-experimental design research method type one group pretest-posttest. The population is 26 students of PPA Ibnu Katsir 2 Jember, with a sample of 9 students. The data collection method used was the Wilcoxon Test. The results of the research show that there is an influence of assertive training to improve psychological well-being at PPA Ibnu Katsir 2 Jember. Assertive training is a training method that is easy for individuals to do. This training emphasizes increasing an individual's ability to communicate socially and avoiding deviant behaviour.Keywords: Assertiveness Training, Psychological Well-Being, Student